2020
DOI: 10.1177/0886260520933037
|View full text |Cite
|
Sign up to set email alerts
|

IPV Characteristics, Childhood Violence, and Adversities as Risk Factors for Being Victimized in Multiple IPV Relationships

Abstract: Empirical knowledge regarding risk factors for intimate partner violence (IPV) from multiple partners (MP) is scarce and sought by clinicians and many women themselves for the prevention of future intimate partner violence relationships (IPVRs). Quantitative data were obtained through a structured interview with a stratified sample of help-seeking women ( N = 154) with no ( n = 48, 0IPVR), one ( n = 55, 1IPVR), or multiple ( n = 51, 2IPVR) IPVRs. This study investigated the association between (a) childhood fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…The significant or trend attachment variables from Step 1 were forwarded to Step 3 where each of them was tested in a separate multivariate logistic regression model adjusted for all remaining sociodemographic and contextual group differences from Step 2 (Model a). In Step 4, we adjusted for childhood adversities, which were found as risk factors in a previous part of this study ( Ørke et al, 2020 ). In two extended models, we adjusted for interaction effects between the attachment factor and each of the childhood adversities.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The significant or trend attachment variables from Step 1 were forwarded to Step 3 where each of them was tested in a separate multivariate logistic regression model adjusted for all remaining sociodemographic and contextual group differences from Step 2 (Model a). In Step 4, we adjusted for childhood adversities, which were found as risk factors in a previous part of this study ( Ørke et al, 2020 ). In two extended models, we adjusted for interaction effects between the attachment factor and each of the childhood adversities.…”
Section: Methodsmentioning
confidence: 99%
“…Other than attachment issues, studies reported childhood risk factors for victimization of IPV. These were in particular psychological abuse/maltreatment ( Cascio et al, 2017 ; McClure & Parmenter, 2017 ; Reyome, 2010 ; Wekerle & Wolfe, 1998 ), sexual ( Ørke, Bjørkly, & Vatnar, 2020 ) and physical abuse (e.g., Barrios et al, 2015 ; Cascio et al, 2017 ; Hetzel-Riggin & Meads, 2011 ), exposure to parental abuse ( Ehrensaft et al, 2003 ; Hetzel-Riggin & Meads, 2011 ; Krishnan et al, 2001 ), and peer victimization ( Ørke et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous research on children and young people has demonstrated how victimisation in one context can link to repeat victimisation as well as victimisation across different contexts, particularly for those that experience multiple forms of victimisation [63]. This could help explain why, for example, women reporting IPVA were also likely to report peer victimisation and childhood sexual abuse [64].…”
Section: Discussionmentioning
confidence: 99%